Green infrastructure codesign from phenomenology: Proposal for small villages in semiarid agricultural lands - Liliana Pérez-Sánchez; Lina Ojeda-Revah; Cristina Barrientos-Durán; Ileana Espejel (Sustainable Environment)
Phenomenology is a paradigm that supports the codesign of green infrastructure (GI) because it integrates intangible aspects that a community perceives. This study aimed to answer the question of how intangible aspects can be expressed in tangible elements in a codesigned rural green infrastructure project. The study case involved a rural village embedded in a semiarid Mediterranean-type landscape in northwestern Mexico. The phenomenological elements perceived by the inhabitants of the selected village were integrated into the village´s urban master plan with several small GI codesigns. Using the snowball method, we interviewed nine people recognized as local stakeholders interested in GI. Concepts such as quality of life, landscape architecture, rural planning, codesign, and GI were addressed in the interviews. GI and ecosystem services were analyzed in this paper. The results revealed intangible issues such as the community trajectory within an agricultural and semiarid landscape, lifestyle connectedness with the environment through pro-environmental behaviors, and values favoring rurality. Collective tangible concerns about water supply, biodiversity alteration, flooding during the rainy season, and lack of bicycle paths, green areas, budgets, and rural‒urban planning were identified and used for the GI codesigns. An adaptation of one of the GI codesigns is under construction. This research proposes the application of phenomenology in codesign microscale planning in other rural settlements in semiarid environments, as it captures the essence of intangible key issues and motivates villagers and authorities to implement GI.